Model Pembangunan Pertanian Pola Interaksi dan Interdependensi dalam Memanfaatkan Fasilitas Pelayanan Sosial Ekonomi di Kabupaten Serdang Bedagai - Gustami Harahap; Fatmawaty Harahap; Erwin Pane (Jurnal Agriuma, 2020)
People often experience problems in their daily activities, especially service problems, such as long queues and long enough public affairs.Â  This problem occurs not only in urban communities but in rural communities also experience the same problem, both socio-economic aspects. This pattern of interaction and interdependence is an effort in order to utilize the socio-economic service facilities that can improve the welfare of rural communities, especially in the farming community which can later utilize the patterns that will be applied in Serdang Bedagai Regency. The approach method used in this research is the Structural Equetion Model (SEM) approach. The main problem examined and examined in this study relates to "Application of patterns of interaction and interdependence of rural communities in Serdang Bedagai Regency, North Sumatra Province.